A review of safety and immunogenicity of a novel measles, mumps, rubella (MMR) vaccine - Nitin Shah; Apurba Ghosh; Kishore Kumar; Trayambak Dutta; Manish Mahajan (Taylor & Francis Group, 2024)
Measles, mumps, and rubella (MMR) are highly infectious viral diseases affecting young children and have high secondary attack rates. Present MMR vaccines show consistent seroconversion rates for anti-measles and anti-rubella antibodies with variable responses for anti-mumps antibodies. Most common strains for MMR vaccines, currently available in India, are the Edmonston-Zagreb measles strain, Leningrad Zagreb (L-Z) mumps strain, and the RA 27/3 rubella strain. L-Z strain of mumps virus has been found to be associated with aseptic meningitis by different studies from different parts of the world including India. Recently, a novel freeze-dried MMR vaccine developed by Zydus Lifesciences (Zyvac MMR) contains Edmonston Zagreb measles strain, Hoshino mumps strain, and RA 27/3 rubella strain. The Hoshino strain is WHO approved and was found to induce interferon gamma production. This review article aims to provide a comprehensive appraisal of the data available on the safety and immunogenicity of the novel MMR vaccine.